Polska i Polacy w poezji autorów piszących po polsku w Izraelu - Żurek, Sławomir Jacek (Postscriptum Polonistyczne, 2020)
The article is an attempt to analyse relations between Polish Jews, the country of their first inhabitancy along with their Polish fellow citizens. It is an extremely complicated matter, because such relations are influenced by their fondness for the lost homeland and resentment felt towards the Poles. The selected poems of the authors, representing different generations, are analysed in the article. They reveal the whole variety of personal experiences and sentiments in a more emotive way than the works of prose. The article consists of two parts entitled: The image of sentiment and The image of resentment. They are based on the poetry of Irit Amiel, Łucja Gliksman, Renata Jabłońska, Szlomo Leser, Aleksander Rozenfeld, Jael Shalitt and Aviva ShavitWładkowska.